2009
DOI: 10.1007/s10803-009-0859-4
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Ultrasound and Risk of Autism Spectrum Disorders

Abstract: We evaluated antenatal ultrasound (U/S) exposure as a risk factor for autism spectrum disorders (ASD), comparing affected singleton children and control children born 1995-1999 and enrolled in the Kaiser Permanente health care system. Among children with ASD (n = 362) and controls (n = 393), 13% had no antenatal exposure to U/S examinations; case-control differences in number of exposures during the entire gestation or by trimester were small and not statistically significant. In analyses adjusted for covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
(51 reference statements)
1
22
1
2
Order By: Relevance
“…Two studies showed that autism births occur in geographical clusters, which could indicate that local factors are involved in the prevalence. 247,256 Another study found that while electromagnetic radiation has been hypothesized to be a risk factor due to biological plausibility, no epidemiological evidence is yet available. 257 Other studies have found no significant association between prenatal exposure to ultrasound and ASD.…”
Section: Othermentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies showed that autism births occur in geographical clusters, which could indicate that local factors are involved in the prevalence. 247,256 Another study found that while electromagnetic radiation has been hypothesized to be a risk factor due to biological plausibility, no epidemiological evidence is yet available. 257 Other studies have found no significant association between prenatal exposure to ultrasound and ASD.…”
Section: Othermentioning
confidence: 99%
“…257 Other studies have found no significant association between prenatal exposure to ultrasound and ASD. 256,258 …”
Section: Othermentioning
confidence: 99%
“…Deux études ont montré que les naissances d'enfants vivant avec l'autisme se produisent par grappes géographiques, ce qui pourrait indiquer que des facteurs locaux interviennent dans la prévalence 247,256 . Une autre étude a montré que même si l'hypothèse que les rayons électromagné-tiques pourraient constituer un facteur de risque est plausible du point de vue biologique, il n'existe encore aucun élé-ment de preuve épidémiologique 257 .…”
Section: Autres Dimensionsunclassified
“…Une autre étude a montré que même si l'hypothèse que les rayons électromagné-tiques pourraient constituer un facteur de risque est plausible du point de vue biologique, il n'existe encore aucun élé-ment de preuve épidémiologique 257 . D'autres études n'ont trouvé aucun lien important entre l'exposition prénatale aux ultrasons et le TSA 256,258 .…”
Section: Autres Dimensionsunclassified
“…2 There is no independently confirmed peer-reviewed published evidence that a cause-effect relationship exists between in utero exposure to clinical ultrasound and development of ASD in childhood from recent high quality studies. [7][8][9] The recent study by Webb et al involves a case series endeavouring to assess factors influencing ASD severity rather than ASD incidence. From 2644 families with one child with ASD aged 4-18 years and one unaffected full sibling, a subgroup of 1749 children who had array comparative genomic hybridisation testing was collected.…”
mentioning
confidence: 99%